Desain dan Pengembangan Lengan Robot SCARA 5-DOF untuk Pendidikan Robotika di Laboratorium STEM - Febrianto, Rokhmat (AI Society & STMIK Indonesia, 2024)
The development of a 5-degree-of-freedom (DOF) SCARA robot arm was successfully achieved for educational use within the CSL Laboratory at the School of Applied STEM, Universitas Prasetiya Mulya. The design utilizes cost-effective, locally sourced materials and an open-source control system based on Processing Java and Arduino C. These features make the SCARA robot arm an accessible tool for students to learn robotics, particularly in the areas of kinematics, control, and programming. Extensive testing of the robot’s inverse kinematics algorithm showed promising results, with average error rates of 1.20% for the Inner Arm, 4.21% for the Outer Arm, and 3.39% for the Z-axis. These low error rates highlight the robot’s precision in movement. This research not only met its objective of creating an accessible platform for teaching robotics but also demonstrated potential for future development in robotics education and industrial applications.